Pengaruh Perbedaan Warna Lampu pada Hasil Tangkapan Ikan Teri (Stolephorus Sp) pada Alat Tangkap Bagan Perahu di Perairan Karangantu Serang Banten - Ibnu Gustiron; Gilang Rusrita Aida; M Tajuddin Noor; Yusrudin Yusrudin (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Boat lift net is a fishing tool that operates at night. This tool has the aim of getting catches in large quantities by using light aids from lamps. This research aims to investigate the effect of different colors of lights on the catch of anchovies (Stolephorus sp) on boat fishing gear in the waters of Karantu Serang, Banten. The experimental fishing method will be used with two different colored lights, namely green and white. Anchovy catch data will be collected and analyzed to evaluate whether there are significant differences in the number of anchovy catches caught in the two different light colors. It is hoped that the results of this research will provide a better understanding of the influence of different colors of lights on the catch of anchovies (Stolephorus sp) on boat fishing gear in the Karangantu waters of Serang, Banten.